Circular and rectangular folk silos in the Andes of Southern Bolivia - Kent, Robert B. (Espacio y Desarrollo, 1998)
This paper documents the presence, characteristics, and distribution of folk silos (crop storage structures) in the southern portion of the department of Cochabamba, Bolivia. Known locally as trojes or silos, these silos are constructed in circular and rectangular plans from adobe and local plant materials. Circular silos are used primarily to store com, while a wider variety of crops, including potatoes, peanuts, wheat, and barley are stored in the rectangular silos. A review of the literature on crop storage structures in the Andean region suggests that the design and use of these present-day silos is likely of Inca origin.